Development of Toast Packaging Design Using Rough Set Theory (RST) Based on Kansei Engineering (KE) - Lytta Yennia Putri; Novi Purnama Sari (Poltanesa, 2025)
The current toast packaging has not met customer satisfaction due to the use of inappropriate packaging materials and unattractive packaging design. Therefore, it is necessary to plan and develop packaging with Kansei Engineering (KE) that is able to translate consumer emotions. It is important to apply the use of elements that are in accordance with the concept. The method of determining the elements used is Rough Set Theory (RST). The result of the concept with the K-Means Genetic Algorithm method is “practical” while the elements produced by the RST method get a horizontal block shape with paper & polymer materials, window features, telescope locks, minimalist design, surface direct and images consisting of vector illustrations. The use of RST in this study proved to be optimal in realizing practical concepts, with supporting elements in the form of horizontal beams that have a support size value of 3 and a Laplace value of 0.887.